Profile of neonatal mortality in the Islamic Republic of Iran in 1391 - Farima Raji (Tehran University Medical Journal, 2016)
Background: The first duty of any government is to ensure the health of its children and neonates. Today's countries are classified as declining mortality in this group. To increase neonatal survival rate, classified causes of newborn mortality are the Core Strategy and Policies. This study was aimed to determine the classification of causes of neonatal death in Iran.